The Plane Wave Methods Combined with Local Spectral Finite Elements for the Wave Propagation in Anisotropic Media (Advances in Applied Mathematics and Mechanics, 2018)
The plane wave least-squares method combined with local spectral finite elementshas been used effectively to solve time-harmonic acoustic and electromagneticwave propagation with complex wavenumbers. We develop the plane wave least-squaresmethod and the ultra weak variational formulation for the nonhomogeneouscase of the electromagnetic wave propagation in anisotropic media. We derive errorestimates of the approximation solutions generated by these methods in one specialcase of TE mode scattering. Numerical results indicate that the resulting approximatesolutions generated by these two methods possess high accuracy and verify the validityof the theoretical results.